Faktor-faktor yang mempengaruhi minat beli konsumen pada cv master pasir pengaraian kabupaten rokan hulu - HELMI, MUHAMMAD SUKRI (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
In this study aims to determine the factors that influence consumer buying interest on the CV. Mastersand Pengaraian consisting of a desire to make a purchase, product selection, product selectionexperience, experience in using the product, use the product, the desire to own the product, quality,taste, easily available and the price. This research is qualitative descriptive research is research thatanalyzes of the answers and then interpreted conclusions. The method used is a method deskrptip andthe level of achievement of the respondents (TCR). The data used are primary and secondary data.This study uses 25 respondents. Saturated with sample collection technique where all the populationsampled is how many people are buying and credit CV Masters in June. Hasi research shows thatTCR or the level of achievement of the respondents in the variable buying interest has a level of 76%of respondents Capain criter ia (good enough). And descriptive analysis of the results of research onfactors affecting consumer buying interest mengugunakan ranking technique is to ask respondentsgiving rank 1-5 on reason respondents chose the product in CV Master Sand Pengaraian. In theranking criteria 1, the factors that most influence the buying interest in CV Master is a factoraccording keebutuhan / tastes. Then in the second rank criteria that factor has often buy products atCV Master. Then at 3 ranking criteria are factors never purchased before. Then in kritria rank 4 thatfactor very high quality products. Later on 5 ranking criteria that factor own desires